Methodology Development of Interactive E- Courses : Pengembangan Metodologi E-Kursus Interaktif - Usmonov Murod Sodiqovich; Abdullayev Xolxuja Burxonovich; Suvonqulov Baxtiyor Mamarasulovich (Universitas Muhammadiyah Sidoarjo, 2020)
This article describes the goals and objectives of creating interactive e-learning courses based on multimedia technologies and develops a methodology for their use in the educational process.